2014
DOI: 10.1155/2014/689826
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Caregiving, and Health: Exploring the Influence of Culture on Family Caregiver Experiences

Abstract: Ethnic minorities are expected to experience a greater demand for family caregiving than non-Latino Whites due to their projected population growth. Although the consensus of researchers on caregiving and culture finds that the caregiving experience differs significantly among cultural/ethnic groups, the question remains as to how cultural values and norms influence the caregiver experiences. We conducted an interpretative, phenomenological qualitative analysis of focus group transcripts from four groups (Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
131
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 35 publications
4
131
1
1
Order By: Relevance
“…Parallels with existing caregiving research on informal caregiving in China are limited. The most relevant studies focus on cultural or ethnic differences among caregivers residing in developed countries (Jones, Zhang, Jaceldo‐Seigl, & Meleis, ; Pharr, Dodge Francis, Terry, & Clark, ; Tang, ; Yeung et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Parallels with existing caregiving research on informal caregiving in China are limited. The most relevant studies focus on cultural or ethnic differences among caregivers residing in developed countries (Jones, Zhang, Jaceldo‐Seigl, & Meleis, ; Pharr, Dodge Francis, Terry, & Clark, ; Tang, ; Yeung et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…90 Furthermore, women, particularly of ethnic minorities, experience a greater demand for family caregiving responsibilities, which in turn is associated with chronic stress, time constraints for self-care, and ultimately poor health outcomes. 91 Improved recognition of barriers to seeking care including time constraints, primary caretaker responsibilities, and psychosocial stress is important. Alternate modes of delivery such as telemedicine or web-based approaches that offer flexible hours and personalized treatment options may be better embraced by women.…”
Section: Recognition Of Other Important Determinants Of Healthmentioning
confidence: 99%
“…A study carried out to explore the inluence of culture on family caregiver experience revealed that among African American, Asian American, Hispanic American, and European American, there were commonalities in the experience of caregiving and the challenges that come with. However, signiicant distinctions appeared in the cultural norms, beliefs and values that shaped the caregiving experience of the people [11]. Cultural diversity across nations has resulted in the diferences observed in the employment of informal caregiving or formal caregiving.…”
Section: Caregiving In Diverse Climes and At Diferent Timesmentioning
confidence: 99%
“…Although home care is a more preferred option for elderly and terminally ill patients, the society, and cultural beliefs also determines the choice of home care for terminally ill patients. In countries ruled by the idea of collectivism, the act of family members caring for their older relatives, their chronically/terminally ill relatives are common [11]. On the other hand, in individualistic societies, there is usually a shift away from informal care in the home for chronically/terminally ill relatives to a more formalized form of care [11].…”
Section: Elderly Patients With Terminal/chronic Illnesses and Their Cmentioning
confidence: 99%
See 1 more Smart Citation